Efficient TCP variant with congestion notification for heterogeneous networks. (22nd June 2009) - Anusuya, K.V.; Krishna Chaitanya, B.; Subha Rani, S.
In wireless networks, the packet loss may occur due to high bit error rate, packet corruption and link failures. The existing implementations of TCP interpret the loss occurrence is only due to congestion. This erratic prediction reduces the flow rate of TCP segments and it directly degrades its performance. The TCP variants like TCP New Jersey and TCP NJ+ achieve improvements in goodput over existing TCP NewReno by distinguishing wireless losses from congestion losses. In this paper, we propose an explicit congestion notification (ECN) enabled negative acknowledgement scheme SNACK-NJ, based on TCP NJ+ to further improve the performance of TCP over wireless networks. The simulation results confirm that the proposed scheme outperforms the conventional TCP implementations.